In Vivo Anthelmintic Efficacy of Adansonia digitata and Anogeissus leiocarpa against Haemonchus contortus Infestation Induced in Sheep - Julienne Kuiseu; Basile Konmy; Christian Cocou Dansou; Tony Taofick Babalola Abiodoun Sounkere; Claude Gbemeho Houssoukpe; Sylvie Mawule Hounzangbe-Adote; Patrick Aleodjrodo Edorh; Pascal Abiodoun Olounlade (Hindawi Limited, 2024)
The aim of the present study was to assay the in vivo anthelminthic activity of Anogeissus leiocarpa (Al) family of the Asteraceae and Adansonia digitata (Ad) family of Malvaceae leaf powder against the nematode Haemonchus contortus (Hc) in sheep. Twenty-eight sheep were artificially infected with 3000 Infective larvae (L3) of Hc and divided into four groups. Groups 1 and 2 received 3.2 g/kg of Ad and Al leaf powder according to the body weight for three days by oral route. This treatment was repeated after 14 days. Group 3 received albendazol 5 mg/kg and group 4 received water. The treatment was repeated 14 days later. Examination of faecal samples, packed cell volume and biochemical analyses and necropsy were carried out to determine egg counts, worm burdens, and reduction in worm fecundity and changes in blood parameters. The results showed a reduction in egg excretion of 72.22% and 88.49%, respectively, with Al and Ad leaf powder. Egg laying of adult female worms was reduced by 55.22% and 64.96% with Ad and Al, respectively. FAMACHA score (≤2 in the treated animals) and packed cell volume were improved with Ad and Al. The results of this study revealed that Ad and Al powder may be used as an alternative anthelminthic to control haemonchosis in small ruminants.